91.3k views
5 votes
G(x) = x2 - 2x +3 for g

User Silverwind
by
6.0k points

1 Answer

6 votes

Answer:

Since

x

is on the right side of the equation, switch the sides so it is on the left side of the equation.

x

2

2

x

+

3

=

G

(

x

)

Multiply

G

by

x

.

x

2

2

x

+

3

=

G

x

Subtract

G

x

from both sides of the equation.

x

2

2

x

+

3

G

x

=

0

Use the quadratic formula to find the solutions.

b

±

b

2

4

(

a

c

)

2

a

Substitute the values

a

=

1

,

b

=

2

G

, and

c

=

3

into the quadratic formula and solve for

x

.

(

2

G

)

±

(

2

G

)

2

4

(

1

3

)

2

1

Simplify.

Tap for more steps...

x

=

2

+

G

±

G

2

+

4

G

8

2

The final answer is the combination of both solutions.

x

=

2

+

G

+

G

2

+

4

G

8

2

x

=

2

+

G

G

2

+

4

G

8

2

Explanation:

User MartinJoo
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.